Taiwan Goverments Responsibility For The Provision of Public Facilities Detrimental To The Community - Muhammad Afif Hidayatulloh; Rafiqi Anjasmara; Imaniar Imaniar (LPPM Universitas PGRI Sumatera Barat, 2019)
This article aims to analyze Taiwan's government accountability for fishermen who are working in the waters of Nanfangao, Taiwan. Jeremy Bentham through his book